Effect of Mechanical Damage to Strawberry Transplants - John R. Duval; Craig K. Chandler; Daniel E. Legard (EDIS, 2003)
The purpose of this study was to determine the influence on performance of traditionally harvested transplants (machine dug) in comparison to transplants which do not undergo the rigors of traditional harvesting (hand dug). This document is HS922, one of a series of the Horticultural Sciences Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published June 2003.